Method for producing (oxy) hydroxides and (oxy) hydroxides
In the manufacturing process of the cathode material of lithium-ion battery, the reaction is performed using a water-soluble salt containing Ni and Co/Mn transition metal and an aqueous solution of alkali metal hydroxide to generate and slurry hydroxide solid particles, which solves the problem that it is difficult to produce a precursor with a narrow particle size distribution and excellent sphericality in the prior art, and achieves a high-performance cathode material precursor.
Patent Information
- Application Number
- CN202380058751.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-11
- Filing Date
- 2023-07-31
- Publication Date
- 2025-03-21
AI Technical Summary
It is difficult to produce a precursor of a lithium-ion battery cathode material with a narrow particle size distribution and excellent sphericality.
By providing an aqueous solution of water-soluble salt containing Ni and Co/Mn transition metals, and an aqueous solution of alkali metal hydroxide, and combining in a stirred tank reactor, solid hydroxide particles are generated and slurried, and the mother liquor containing slurried hydroxide particles is taken out using a solid-liquid separation device.
The production of precursors with narrow particle size distribution and excellent sphericality is achieved, and the performance of the cathode material of lithium-ion battery is improved.
Smart Images

Figure BDA0005265682220000171 
Figure BDA0005265682220000172 
Figure HDA0005265682230000011
Abstract
Description
[0001] The present invention relates to a process for the manufacture of a granular (oxy)hydroxide of TM, wherein it is a combination of nickel and at least one metal selected from Co and Mn, and wherein the process comprises the following steps:
[0002] (a) providing an aqueous solution (α) of one or more water-soluble salts containing Ni and at least one transition metal selected from Co and Mn and optionally at least one additional metal selected from Ti, Zr, Mo, W, Al, Mg, Nb and Ta and an aqueous solution (β) containing an alkali metal hydroxide and optionally an aqueous solution (γ) containing a complexing agent,
[0003] (b) combining solution (α) and solution (β) and, if applicable, solution (γ) in a stirred tank reactor at a pH value in the range of 10.5 to 12.5 determined at 23° C. in one or more sub-steps, thereby forming solid particles of the hydroxide, said solid particles being slurried,
[0004] The stirred tank reactor used in step (b) or in at least one of these sub-steps (b) is equipped with a solid-liquid separation device, through which a mother liquor containing slurried hydroxide particles in the range of 2 mg / l to 20 g / l is taken off.
[0005] Lithiated transition metal oxides are currently used as electrode active materials for lithium-ion batteries. A great deal of research and development work has been done over the past few years to improve properties like charge density, specific energy, and also other properties (like cycle life reduction and capacity loss) that may adversely affect the life or applicability of lithium-ion batteries. Additional efforts have been made to improve manufacturing methods.
[0006] In a typical method for making cathode materials for lithium-ion batteries, a so-called precursor is first formed by coprecipitating a transition metal as a carbonate, an oxide, or preferably as a hydroxide (e.g., an oxyhydroxide) which may or may not be alkaline. The precursor is then mixed with a lithium source (such as, but not limited to, LiOH, Li2O, or Li2CO3) and calcined (fired) at high temperature. One or more lithium salts may be used as one or more hydrates or in a dehydrated form. Calcination (or firing) - also often referred to as thermal treatment or heat treatment of the precursor - is typically carried out at a temperature in the range of 600°C to 1000°C. Solid-state reactions occur during the thermal treatment and electrode active materials are formed. The thermal treatment is carried out in the heating zone of an oven or kiln.
[0007] To some extent, the properties of the precursor are converted into the properties of the corresponding electrode active material, such as particle size distribution, content of the corresponding transition metal, etc. Therefore, the properties of the electrode active material can be influenced by controlling the properties of the precursor.
[0008] Cathode active materials with narrow particle size distribution - and therefore their precursors - have been the object of research. In EP 2 720 305 A, a two-step process is disclosed, in which the pH is lowered relative to the first step in the second step (the so-called particle growth step). In EP 2 818 452 A, a two-step process is disclosed, in which a mother liquor is withdrawn in the particle growth step. Note that no solids are withdrawn with the mother liquor.
[0009] It is an object of the present invention to provide a method that allows the production of highly spherical precursors with a narrow particle size distribution. Another object of the present invention is to provide a precursor for an electrode active material having a narrow particle size distribution and excellent sphericity.
[0010] Thus, a method as defined at the outset has been found, hereinafter also defined as "the method of the invention" or "the method according to the (present) invention". The method of the invention comprises at least two steps, hereinafter also referred to as step (a) and step (b), or - even more simply - as (a), and (b), respectively. The method of the invention may comprise further - optional - steps. Steps (a) and (b) are described in more detail below. A highly spherical precursor having a narrow particle size distribution is obtained by the method of the invention.
[0011] It has been found that - if in step (b) a certain amount of particles is also removed via the clarifier - the span of the obtained particulate (oxy)hydroxide of TM is in the range of 0.20 to 0.33.
[0012] The method of the invention is a method for producing a particulate (oxy)hydroxide of a TM. The particulate (oxy)hydroxide then serves as a precursor for an electrode active material, and it may therefore also be referred to as a precursor.
[0013] In one embodiment of the present invention, the resulting precursor comprises secondary particles which are agglomerates of primary particles. The primary particles have the shape of flakes.
[0014] In one embodiment of the present invention, the specific surface area (BET) of the resulting precursor is determined by nitrogen adsorption, for example according to DIN-ISO 9277:2003-05, in the range of 2 to 70 m 2 The degassing temperature was 120°C.
[0015] The precursor is an (oxy)hydroxide of TM, wherein TM comprises Ni and at least one metal selected from Co and Mn and Al and optionally at least one further metal selected from Ti, Zr, Mo, W, Mg and Nb.
[0016] In one embodiment of the present invention, TM is a metal combination according to formula (I)
[0017] (Ni a Co b Mn c ) 1-d M d (I)
[0018] in
[0019] a is in the range of 0.6 to 0.95, preferably 0.8 to 0.94,
[0020] b is in the range of 0.025 to 0.2, preferably 0.025 to 0.15,
[0021] c is in the range of 0 to 0.2, preferably 0 to 0.15, and
[0022] d is in the range of 0 to 0.1,
[0023] M is selected from the group consisting of Mg, Al, Ti, Zr, Mo, W, Nb and Ta,
[0024] a+b+c=1 and b+c>0, or M includes Al and d>0.
[0025] In another embodiment of the present invention, TM corresponds to the general formula (Ia)
[0026] (Ni a Co b Mn c ) 1-d M d (I a)
[0027] in
[0028] a is in the range of 0.25 to 0.4,
[0029] b is in the range of 0 to 0.2,
[0030] c is in the range of 0.6 to 0.75, and
[0031] d is in the range of 0 to 0.1,
[0032] M is selected from the group consisting of Mg, Al, Ti, Zr, Mo, W, Nb and Ta,
[0033] a+b+c=1.
[0034] In each case, the TM may contain traces of additional metal ions, for example traces of ubiquitous metals such as sodium, iron, calcium or zinc as impurities, but such traces will not be considered in the description of the present invention. Trace amounts in this case will mean amounts of 0.05 mol-% or less relative to the total metal content of the TM.
[0035] The precursor is a granular material. In one embodiment of the present invention, the precursor has an average particle size (D50) in the range of 3 to 20 μm, preferably 4 to 16 μm. The average particle size can be determined, for example, by light scattering or laser diffraction or electroacoustic spectroscopy. The above particle size refers to the secondary particle diameter.
[0036] The span of the particle size distribution of the precursor is in the range of 0.20 to 0.33, preferably 0.21 to 0.29. The span is defined as [(D90) - (D10)] / (D50), where the values of (D90), (D50) and (D10) are determined by dynamic light scattering.
[0037] The granular material may have an irregular shape, but in a preferred embodiment, the granular material has a regular shape, such as a spherical or even spherical shape. The aspect ratio may be in the range of 1 to 10, preferably 1 to 3 and even more preferably 1 to 1.5. The aspect ratio is defined as the ratio of width to length, or specifically, the ratio of the particle diameter in the longest dimension to the particle diameter in the shortest dimension. A perfectly spherical particle has an aspect ratio of 1.
[0038] Step (a) comprises providing at least one aqueous solution (α) containing Ni and at least one transition metal selected from Co and Mn and optionally at least one additional metal selected from Ti, Zr, Mo, W, Al, Mg, Nb and Ta and an aqueous solution (β) containing an alkali metal hydroxide and optionally an aqueous solution (γ) containing a complexing agent such as ammonia.
[0039] The term water-soluble salt of cobalt and nickel or manganese or metals other than nickel, cobalt and manganese refers to a salt exhibiting a solubility of 25 g / l or more in distilled water at 25° C., the amount of salt being determined ignoring water of crystallization and water from aquo complexes. The water-soluble salt of nickel, cobalt and manganese may preferably be Ni 2+ and Co 2+ and Mn 2+ Examples of water-soluble salts of nickel and cobalt are sulfates, nitrates, acetates and halides, especially chlorides. Preferred are nitrates and sulfates, with sulfates being more preferred.
[0040] The term "water-soluble compound of aluminum" refers to compounds such as Al2(SO4)3, Al(NO3)3, KAl(SO4)2, NaAlO2 and NaAl(OH)4. Depending on the choice of the water-soluble compound of aluminum, the pH value of the aqueous solution (α) can be in the range of 1 to 3 or above 13.
[0041] Examples of suitable Mg compounds are MgSO4, Mg(NO3)2, magnesium acetate and MgCl2, among which MgSO4 is preferred.
[0042] Examples of suitable Ti compounds are Ti(SO4)2, TiOSO4, TiO(NO3)2, Ti(NO3)4, among which Ti(SO4)2 is preferred.
[0043] Examples of suitable Zr compounds are zirconium acetate, Zr(SO4)2, ZrOSO4, ZrO(NO3)2, Zr(NO3)4, among which Zr(SO4)2 is preferred.
[0044] Examples of suitable Nb compounds are (NH4)Nb(C2O4)3 and (NH4)NbO(C2O4)2. Examples of suitable Mo compounds are MoO3, Na2MoO4 and (NH4)2MoO4.
[0045] Examples of suitable W compounds are WO3, WO3.H2O, Na2WO4, ammonium tungstate and tungstic acid.
[0046] The solution (α) may have a pH in the range of 2 to 5. In embodiments where a higher pH is desired, ammonia may be added to the solution (α). However, ammonia is preferably not added to the solution (α). In the case where it is intended to provide a solution containing NaAlO2 and NaAl(OH)4, it is preferred to provide at least two aqueous solutions, one containing nickel and at least one of cobalt and manganese and optionally at least one of Ti, Zr, Mo, W, Mg, Nb and Ta, and the other aqueous solution containing NaAlO2 or NaAl(OH)4.
[0047] The concentration of nickel and other components of TM (as appropriate) can be selected within a wide range. Preferably, the corresponding total metal concentration is selected to be in the range of 1 to 1.8 mol metal / kg solution, more preferably 1.3 to 1.7 mol metal / kg solution.
[0048] Furthermore, an aqueous solution of an alkali metal hydroxide is provided in step (a), hereinafter also referred to as solution (β). Examples of alkali metal hydroxides are potassium hydroxide and a combination of sodium hydroxide and potassium hydroxide, and even more preferably sodium hydroxide.
[0049] In one embodiment of the present invention, the solution (β) mainly contains alkali metal hydroxide and a certain amount (e.g., 0.1% to 2% by weight relative to the corresponding amount of alkali metal hydroxide) of carbonate added intentionally or by aging the solution (β) or the corresponding alkali metal hydroxide.
[0050] The solution (β) may have a hydroxide concentration in the range of 0.1 to 12 mol / l, preferably 6 to 10 mol / l.
[0051] The pH value of the solution (β) is preferably 13 or higher, for example 14.5.
[0052] The solution (γ) contains a complexing agent. Examples of complexing agents are ammonia and organic acids or their alkali or ammonium salts, wherein the organic acid carries at least two functional groups per molecule and at least one of these functional groups is a carboxylate group.
[0053] Examples of organic acids with two identical functional groups are adipic acid, oxalic acid, succinic acid and glutaric acid.An example of an organic acid with three identical functional groups is citric acid.
[0054] In one embodiment of the present invention, the organic acid is selected from malic acid, tartaric acid, citric acid and glycine.
[0055] In one embodiment of the present invention, the concentration of the complexing agent in the solution (γ) is in the range of 1% to 30% by weight. In the embodiment in which the complexing agent is selected from ammonia, the concentration of the complexing agent is preferably in the range of 10% to 30% by weight. In the embodiment in which the complexing agent is selected from an organic acid or an alkali salt or an ammonium salt thereof, wherein the organic acid carries at least two functional groups per molecule and at least one of these functional groups is a carboxylate group, the concentration of the complexing agent in the solution (γ) may be in the range of 0.2% to 10% by weight.
[0056] A more preferred complexing agent is ammonia.
[0057] Step (b) comprises combining solution (α) and solution (β) and, if applicable, solution (γ) in a stirred tank reactor at a pH value in the range of 10.5 to 12.5 determined at 23° C. in one or more sub-steps, thereby generating solid particles of the hydroxide. The solid particles are slurried. Step (b) is preferably carried out as a discontinuous process.
[0058] In embodiments where step (b) is performed in a single sub-step (which may also be referred to as "in a single step" or "in a single operation"), step (b) is preferably performed at a constant pH value.
[0059] In embodiments in which step (b) is carried out in at least two sub-steps (hereinafter also referred to as sub-step (b1), sub-step (b2), and, if applicable, sub-step (b3), etc.), at least two sub-steps (e.g., sub-steps (b1) and (b2)) are carried out at different pH values, e.g., at pH values that differ by 0.2 to 1.5 units (each determined at 23°C).
[0060] In one embodiment of the present invention, this seed step (b1) comprises combining solution (α) and solution (β) and, if applicable, solution (γ) in a continuously operated stirred tank reactor at a pH value in the range of 12.0 to 12.5 determined at 23° C., thereby generating solid particles of the hydroxide, said solid particles being slurried, and
[0061] Sub-step (b2) comprises transferring the slurry from step (b) into a stirred tank reactor, in which solution (α) and solution (β) and, if applicable, solution (γ) are combined with the slurry at a pH value in the range of 11.0 to 12.0 determined at 23° C.,
[0062] And wherein the stirred tank reactor used in sub-step (b2) is equipped with a solid-liquid separation device, through which the mother liquor containing slurried hydroxide particles in the range of 2 mg / l to 20 g / l is taken out.
[0063] In one embodiment of the present invention, the particles produced by step (b1) have an average diameter (D50) in the range of 1 to 6 μm.
[0064] In one embodiment of the present invention, the residence time of the slurry in step (b1) is in the range of 10 minutes to 6 hours, preferably in the range of 30 minutes to 9 hours, more preferably in the range of 4 to 8 hours. Step (b1) can be carried out in a continuous or discontinuous mode, preferably discontinuous.
[0065] In one embodiment of the present invention, step (b) is carried out at a temperature in the range of 10°C to 85°C, preferably in the range of 20°C to 70°C.
[0066] In one embodiment of the invention, step (b) is carried out at constant pressure, for example at ambient pressure. In other embodiments, step (b) is carried out at elevated pressure, for example up to 50 bar.
[0067] In one embodiment, to carry out sub-step (b2), the slurry from sub-step (b1) is transferred to a stirred tank reactor, in which solution (α) and solution (β) and, if applicable, solution (γ) are combined with the slurry at a pH value in the range of 11.0 to 12.0 determined at 23° C. Preferably, the pH value in sub-step (b2) is lower than in step (b1), for example by at least 0.2 units and more preferably by at least 0.3 units.
[0068] The transfer can be carried out immediately after the slurry is formed or after a maturation time in a storage container (see below).
[0069] In one embodiment of the invention, the solid content of the slurry transferred to sub-step (b2) - or to a storage container, see below - is in the range of 200 to 1200 g / l. Before sub-step (b2) begins, the slurry from step (b1) is preferably diluted to 2 to 100 g / l in the reactor in which sub-step (b2) is carried out (e.g. with deionized water or with mother liquor). The solid content can be determined by density measurement or ICP (inductively coupled plasma) or by Coriolis measuring instrument and refers to the slurried particles. Dissolved compounds, such as but not limited to Na2SO4, are ignored in this case.
[0070] In one embodiment of the invention, step (b) is carried out under an inert atmosphere, for example nitrogen or a noble gas such as argon. Oxygen-depleted air (e.g. with up to 2% by weight of O2) is also feasible, especially when the TM does not contain manganese. Due to the strong alkalinity of the solution (β), CO2 is not a suitable atmosphere.
[0071] In one embodiment, in sub-step (b2), the slurry from sub-step (b1) is transferred to a stirred tank reactor operated in batch mode, wherein solution (α) and solution (β) and, if applicable, solution (γ) are combined with the slurry at a pH in the range of 11.0 to 12.0. The pH is determined at 23°C.
[0072] The solutions (α) and (β) and, if applicable, (γ) in sub-step (b2) are as defined above. These solutions may have the same or different compositions throughout the time of step (b) - but within the framework of the definition as described above, for example, one of these solutions contains a water-soluble salt of at least one of nickel and cobalt and manganese. In such a case, these solutions are also referred to as solutions (α') and (β') and, if applicable, (γ'), respectively. However, preferably, the composition of solution (α) remains constant in composition in step (b).
[0073] Even more preferably, during step (b), the composition of solution (α) and the composition of solution (β) remain constant.
[0074] The stirred tank reactor used in step (b) or in particular in substep (b2) is equipped with a solid-liquid separation device, through which the mother liquor containing slurried hydroxide particles in the range of 0.002 to 20 g / l is removed. This means that the slurried particles are removed from the stirred tank reactor together with the mother liquor and are not sent back.
[0075] This can be accomplished by intentionally exceeding the capacity of commercially available clarifiers.In embodiments where membranes are used for solid-liquid separation, the mesh size is selected to be larger than the average particle size of the hydroxide being slurried.
[0076] The particles removed during step (b), and in particular in substep (b2), may have a broad particle size distribution, for example 0.2 to 20 μm, and these particles may have a span of 0.3 to 1.0.
[0077] In one embodiment, the composition of the solution (α) - or (α'), as the case may be - varies during sub-step (b2), for example, the concentrations of nickel and cobalt or manganese. In another embodiment of the invention, the composition of the solution (α) - or (α'), as the case may be - remains constant.
[0078] In one embodiment of the present invention, the duration of sub-step (b2) is in the range of 30 minutes to 80 hours, preferably in the range of 10 to 70 hours, more preferably in the range of 15 to 60 hours.
[0079] In one embodiment of the present invention, sub-step (b2) is carried out at a temperature in the range of 10°C to 85°C, preferably in the range of 20°C to 70°C.
[0080] In one embodiment of the invention, sub-step (b2) is carried out at constant pressure, for example at ambient pressure. In other embodiments, step (b) is carried out at elevated pressure, for example up to 50 bar.
[0081] In one embodiment of the present invention, the process of the present invention is carried out in a cascade of at least two stirred tank reactors, the first of the at least two stirred tank reactors being equipped with an overflow system, through which the slurry is removed from the first stirred tank reactor and transferred directly or indirectly to the second stirred tank reactor.
[0082] In a preferred embodiment, the slurry is removed from the continuous stirred tank reactor in which step (b) is carried out and transferred to a stirred storage container, in which the slurry is stored under stirring for a period of 15 minutes to 24 hours, preferably 30 minutes to 10 hours, and then transferred to the second stirred tank reactor. Said operation is also referred to as a storage step. During the storage step, neither solution (α) nor solution (β) nor solution (γ) is added. The storage is preferably under an inert gas (see above).
[0083] In one embodiment of the present invention, the temperature during the storing step is in the range of 20 to 70°C, preferably 30 to 70°C.
[0084] In one embodiment of the present invention, the pH of the slurry in the storage container is in the range of 10.0 to 13.0, preferably 11.0 to 12.0, determined at 23°C.
[0085] In one embodiment of the present invention, at the same time, 5 to 30 vol-%, preferably 10 to 20 vol-% of the slurry is in the storage container and 70 to 95 vol-%, preferably 80 to 90 vol-% of the slurry is in the tank reactor in which step (b) is carried out. In this case, the amount of slurry located in any pipe or related parts is ignored.
[0086] In one embodiment of the invention, the slurry in the storage container is occasionally stirred, for example using an average energy input of 0.2 to 1 W / l. Such occasional stirring may be used to avoid settling of solids of the slurry.
[0087] Sub-step (b2) may be followed by further steps, such as a post-treatment step I. An example of a post-treatment step I is the removal of particles of (oxy)hydroxide by solid-liquid separation methods, such as filtration.
[0088] In such a step I, the particles from substep (b2) are separated from the liquid phase by a solid-liquid separation method, preferably by filtration or in a centrifuge. The liquid phase may also be referred to as mother liquor. The filtration may be carried out, for example, on a belt filter or in a filter press.
[0089] In order to remove the mother liquor, the filter cake is preferably washed, for example with water or with an alkali metal hydroxide or alkali metal carbonate solution.
[0090] Filtration can be supported by suction or by pressure.
[0091] Step I can be carried out at any temperature where water is in liquid form, for example 5°C to 95°C, preferably 20°C to 60°C.
[0092] By carrying out step I, a solid material is obtained which is a particulate (oxy)hydroxide or oxide of TM. The material generally has a high water content (e.g. 1% to 30% by weight) and can be dried, for example in air at a temperature in the range of 80°C to 150°C or under reduced pressure ("in vacuum") to a moisture content in the range of 100 to 5,000 ppm, ppm being ppm by weight. The water content can be determined by drying in vacuum at a temperature of 100°C until the weight remains constant. The moisture content can be determined by Karl-Fischer titration.
[0093] After step I or drying, the particulate (oxy)hydroxide or oxide of the TM may be subjected to step (d). Step (d) comprises subjecting the solid from step I to heat treatment in a rotary kiln or in a flash calciner.
[0094] In one embodiment of step (d), the wet solid material is introduced into the rotary kiln through a chute or a vibrating chute, through a worm conveyor or a screw conveyor, preferably through a screw conveyor having a single screw or multiple screws.
[0095] Another aspect of the present invention relates to a particulate (oxy)hydroxide of TM, hereinafter also referred to as the (oxy)hydroxide of the present invention or the precursor of the present invention. The precursor of the present invention is advantageously produced according to the process of the present invention.
[0096] In the (oxy)hydroxide of the present invention, TM refers to a combination of nickel and at least one metal selected from cobalt and manganese, wherein the (oxy)hydroxide of the present invention has an average particle size (d50) in the range of 3 to 20 μm, preferably 4 to 16 μm, and a core-shell structure, wherein both the core and the shell exhibit a substantially radial alignment of the plate-like primary particles and wherein the core and the shell are separated by a porous layer containing randomly arranged primary particles.
[0097] The porous layer can be detected by scanning electron microscopy ("SEM") or transmission electron microscopy ("TEM"). In the porous layer, usually only a few voids can be detected. Preferably, the porous layer between the core and the shell has an average thickness in the range of 0.1 to 1.0 μm.
[0098] The fraction of radially aligned primary particles can be determined, for example, by performing SEM (scanning electron microscopy) on cross sections of at least 5 secondary particles.
[0099] "Substantially radially aligned" does not require perfect radial orientation, but includes deviations from perfect radial orientation of up to 5 degrees in SEM analysis.
[0100] Furthermore, at least 70% of the secondary particle volume is filled with radially oriented primary particles. Preferably, only a smaller inner portion of the volume of those particles, e.g. up to 30%, preferably up to 20%, is filled with non-radially oriented primary particles, e.g. randomly oriented primary particles.
[0101] In the porous layer, preferably, the fraction of voids is greater than 10% if determined by selecting 5 representative particles in SEM and calculating
[0102] The (oxy)hydroxides of the invention have a particle size distribution with a span [(D90) - (D10)] / (D50) in the range of 0.2 to 0.33, preferably 0.21 to 0.29. The diameters (D10), (D50) and (D90) can be determined by dynamic light scattering and refer to the corresponding percentiles.
[0103] In one embodiment of the present invention, the TM in the (oxy)hydroxide of the present invention is a metal combination according to the general formula (I):
[0104] (Ni a Co b Mn c ) 1-d M d (I)
[0105] in
[0106] a is in the range of 0.6 to 0.95, preferably 0.8 to 0.94,
[0107] b is in the range of 0.025 to 0.2,
[0108] c is in the range of 0 to 0.2, and
[0109] d is in the range of 0 to 0.1,
[0110] M is selected from the group consisting of Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb and Ta,
[0111] a+b+c=1.
[0112] In another embodiment of the present invention, the TM in the (oxy)hydroxide of the present invention is a metal combination according to the general formula (Ia):
[0113] (Ni a Co b Mn c ) 1-d M d (I a)
[0114] in
[0115] a is in the range of 0.25 to 0.4,
[0116] b is in the range of 0 to 0.2,
[0117] c is in the range of 0.6 to 0.75, and
[0118] d is in the range of 0 to 0.1,
[0119] M is selected from the group consisting of Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb and Ta,
[0120] a+b+c=1.
[0121] The (oxy)hydroxides of the invention are preferably obtained by the process of the invention.
[0122] The (oxy)hydroxides of the present invention are excellent precursors for cathode active materials suitable for producing batteries with high volumetric energy density and excellent cycle stability. Such cathode active materials are made by mixing with a lithium source (e.g., LiOH or Li2O2 or Li2CO3) and then calcining (e.g., at a temperature in the range of 600°C to 1000°C). In particular, in embodiments in which the TM of the (oxy)hydroxide of the present invention corresponds to formula (I), the calcination is preferably carried out in an atmosphere of oxygen or oxygen-enriched air, for example, having at least 60 vol-% oxygen, preferably 80 vol-% oxygen, and more preferably at least 90 vol-% oxygen. In embodiments in which the TM of the (oxy)hydroxide of the present invention corresponds to formula (I a), the calcination can be carried out in an air atmosphere.
[0123] Examples of suitable arrangements for the calcination are rotary kilns, roller hearth kilns and pusher kilns.
[0124] In one embodiment of the present invention, the temperature is gradually increased and then reaches the desired temperature of 700° C. to 1000° C., preferably 750° C. to 900° C. For example, the mixture of the precursor and the lithium source and the oxide or hydroxide of Al is first heated to a temperature of 350° C. to 550° C. and then kept constant for a period of 10 minutes to 4 hours, and then increased to 650° C. up to 1000° C., preferably 650° C. to 850° C.
[0125] In embodiments where at least one solvent is used in the mixing step, such solvent is removed as part of the step, for example by filtering, evaporating or distilling such solvent. Evaporation and distillation are preferred.
[0126] In one embodiment of the invention, the calcination is carried out in a roller hearth kiln, a pusher kiln or a rotary kiln or a combination of at least two of the foregoing. The advantage of a rotary kiln is that the homogeneity of the material produced therein is very good. In roller hearth kilns and pusher kilns, different reaction conditions for the different steps can be easily set. In laboratory scale tests, box furnaces and tube furnaces as well as split tube furnaces are also feasible.
[0127] By carrying out the calcination method of the present invention, a cathode active material having excellent properties and a narrow particle size distribution can be obtained by a simple method. Preferably, the electrode active material thus obtained has a particle size distribution in the range of 0.1 to 0.8 μm determined according to DIN-ISO 9277:2003-05. 2 The specific surface area (BET) is in the range of 1.1767 W / g.
[0128] Another aspect of the present invention relates to a cathode active material, also referred to hereinafter as the cathode active material of the present invention. The cathode active material of the present invention is composed of the chemical formula Li1 +x TM 1-x O2 description, wherein TM is as defined above, and x is in the range of 0 to 0.05, preferably 0.01 to 0.03, and the cathode active materials have a span in the range of 0.20 to 0.33, preferably 0.21 to 0.29.
[0129] By conducting calcination in the above manner, substantially radially aligned primary particles, for example to at least 80%, preferably to at least 90%, are retained, and a cathode active material having excellent capacity retention is obtained.
[0130] Another aspect of the present invention relates to an electrode and in particular to a cathode, also referred to hereinafter as the cathode of the present invention. The cathode of the present invention comprises
[0131] (A) at least one cathode active material according to the present invention,
[0132] (B) carbon in an electrically conductive form,
[0133] (C) at least one adhesive.
[0134] In a preferred embodiment of the present invention, the cathode of the present invention comprises
[0135] (A) 80 to 99% by weight of the cathode active material of the present invention,
[0136] (B) 0.5 to 19.5% by weight of carbon,
[0137] (C) 0.5 to 9.5% by weight of a binder polymer,
[0138] Percentages are relative to the sum of (A), (B), and (C).
[0139] The cathode according to the invention contains conductive modified carbon, also referred to as carbon (B) for short. Carbon (B) can be selected from soot, activated carbon, carbon nanotubes, graphene and graphite. Carbon (B) can be added as is during the preparation of the electrode material according to the invention.
[0140] The electrodes according to the present invention may comprise additional components. They may include a current collector (D), such as but not limited to an aluminum foil. They further comprise a binder polymer (C), hereinafter also referred to as a binder (C). The current collector (D) is not further described herein.
[0141] Suitable binders (C) are preferably selected from organic (co)polymers. Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected from (co)polymers obtainable, for example, by anionic, catalytic or free radical (co)polymerization, in particular from polyethylene, polyacrylonitrile, polybutadiene, polystyrene, and copolymers of at least two comonomers selected from ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene. Polypropylene is also suitable. In addition, polyisoprene and polyacrylates are also suitable. Polyacrylonitrile is particularly preferred.
[0142] In the context of the present invention, polyacrylonitrile is understood to mean not only polyacrylonitrile homopolymers but also copolymers of acrylonitrile with 1,3-butadiene or styrene. Polyacrylonitrile homopolymers are preferred.
[0143] In the context of the present invention, polyethylene is understood to mean not only homopolyethylene but also copolymers of ethylene, which copolymers contain at least 50 mol % of copolymerized ethylene and up to 50 mol % of at least one further comonomer, for example α-olefins such as propylene, butene (1-butene), 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-pentene, and also isobutylene, vinyl aromatics such as styrene, and also C1-C2 (meth)acrylic acid, vinyl acetate, vinyl propionate, C1-C2 (meth)acrylic acid ... 10 - Alkyl esters, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also maleic acid, maleic anhydride and itaconic anhydride. The polyethylene may be HDPE or LDPE.
[0144] In the context of the present invention, polypropylene is understood to mean not only homopolypropylene, but also copolymers of propylene, these copolymers comprising at least 50 mol% of copolymerized propylene and up to 50 mol% of at least one further comonomer, for example ethylene and α-olefins such as butene, 1-hexene, 1-octene, 1-decene, 1-dodecene and 1-pentene. The polypropylene is preferably isotactic or substantially isotactic polypropylene.
[0145] In the context of the present invention, polystyrene is understood to mean not only homopolymers of styrene but also C1-C12 copolymers with acrylonitrile, 1,3-butadiene, (meth)acrylic acid, (meth)acrylic acid, and the like. 10 - copolymers of alkyl esters, divinylbenzene, especially 1,3-divinylbenzene, 1,2-diphenylethylene and α-methylstyrene.
[0146] Another preferred binder (C) is polybutadiene.
[0147] Other suitable binders (C) are selected from polyethylene oxide (PEO), cellulose, carboxymethylcellulose, polyimide and polyvinyl alcohol.
[0148] In one embodiment of the present invention, the binder (C) is selected from a group consisting of binders having an average molecular weight M in the range of 50,000 to 1,000,000 g / mol, preferably to 500,000 g / mol. w Those (co)polymers.
[0149] The binder (C) may be a cross-linked or non-cross-linked (co)polymer.
[0150] In a particularly preferred embodiment of the present invention, binder (C) is selected from halogenated (co) polymers, especially fluorinated (co) polymers. Halogenated or fluorinated (co) polymers are understood to mean those (co) polymers comprising at least one (co) polymerized (co) monomer having at least one halogen atom or at least one fluorine atom per molecule, more preferably at least two halogen atoms or at least two fluorine atoms per molecule. Examples are polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer and ethylene-chlorofluoroethylene copolymer.
[0151] Suitable binders (C) are, in particular, polyvinyl alcohol and halogenated (co)polymers, for example polyvinyl chloride or polyvinylidene chloride, in particular fluorinated (co)polymers such as polyvinyl fluoride and in particular polyvinylidene fluoride and polytetrafluoroethylene.
[0152] Another aspect of the invention is an electrochemical cell comprising
[0153] (1) a cathode comprising the cathode active material (A) of the present invention, carbon (B) and a binder (C),
[0154] (2) an anode, and
[0155] (3) At least one electrolyte.
[0156] Embodiments of the cathode (1) have been described in detail above.
[0157] The anode (2) may contain at least one anode active material, such as carbon (graphite), TiO2, lithium titanium oxide, silicon or tin. The anode (2) may additionally include a current collector, such as a metal foil such as copper foil.
[0158] The electrolyte (3) may contain at least one non-aqueous solvent, at least one electrolyte salt and optionally additives.
[0159] The nonaqueous solvent of the electrolyte (3) may be liquid or solid at room temperature and is preferably selected from polymers, cyclic or acyclic ethers, cyclic or acyclic acetals, and cyclic or acyclic organic carbonates.
[0160] Examples of suitable polymers are in particular polyalkylene glycols, preferably polyC1-C4-alkylene glycols, and in particular polyethylene glycol. Here, the polyethylene glycol may contain up to 20 mol % of one or more C1-C4-alkylene glycols. The polyalkylene glycol is preferably a polyalkylene glycol with two methyl or ethyl end caps.
[0161] The molecular weight M of suitable polyalkylene glycols and in particular suitable polyethylene glycols is w It may be at least 400 g / mol.
[0162] The molecular weight M of suitable polyalkylene glycols and in particular suitable polyethylene glycols is w It may be up to 5,000,000 g / mol, preferably up to 2,000,000 g / mol.
[0163] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, of which 1,2-dimethoxyethane is preferred.
[0164] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.
[0165] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.
[0166] Examples of suitable cyclic acetals are 1,3-dioxane and in particular 1,3-dioxolane.
[0167] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate.
[0168] Examples of suitable cyclic organic carbonates are compounds of the general formula (II) and (III)
[0169]
[0170] Where R 1 , R 2 and R 3 may be identical or different and are selected from hydrogen and C1-C4-alkyl, for example methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, wherein R 2 and R 3 Preferably not all are tert-butyl.
[0171] In a particularly preferred embodiment, R 1 is methyl and R 2 and R 3 Each is hydrogen, or R 1 , R 2 and R 3 Each is hydrogen.
[0172] Another preferred cyclic organic carbonate is vinylene carbonate, formula (IV).
[0173]
[0174] The solvent(s) are preferably used in anhydrous state, ie with a water content in the range from 1 ppm to 0.1% by weight, which can be determined, for example, by Karl-Fischer titration.
[0175] The electrolyte (3) further comprises at least one electrolyte salt. Suitable electrolyte salts are in particular lithium salts. Examples of suitable lithium salts are LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(C n F 2n+1 SO2)3, lithium imide such as LiN(C n F 2n+1 SO2)2, wherein n is an integer in the range of 1 to 20, LiN(SO2F)2, Li2SiF6, LiSbF6, LiAlCl4 and compounds having the general formula (C n F 2n+1 SO2) t Salts of YLi, wherein m is defined as follows:
[0176] When Y is selected from oxygen and sulfur, t=1,
[0177] When Y is selected from nitrogen and phosphorus, t=2, and
[0178] When Y is selected from carbon and silicon, t=3.
[0179] Preferred electrolyte salts are selected from LiC(CF3SO2)3, LiN(CF3SO2)2, LiPF6, LiBF4, LiClO4, among which LiPF6 and LiN(CF3SO2)2 are particularly preferred.
[0180] In a preferred embodiment of the present invention, the electrolyte (3) contains at least one flame retardant. Available flame retardants can be selected from trialkyl phosphates (the alkyl groups are different or the same), triaryl phosphates, alkyl dialkyl phosphonates and halogenated trialkyl phosphates. Preferred are tri-C1-C4-alkyl phosphates (the C1-C4-alkyl groups are different or the same), tribenzyl phosphate, triphenyl phosphate, phosphonic acid C1-C4-alkyl di-C1-C4-alkyl esters and fluorinated tri-C1-C4-alkyl phosphates.
[0181] In a preferred embodiment, the electrolyte (3) comprises at least one flame retardant selected from trimethyl phosphate, CH3-P(O)(OCH3)2, triphenyl phosphate and tris-(2,2,2-trifluoroethyl)-phosphate.
[0182] The electrolyte (3) may contain 1 to 10% by weight of a flame retardant based on the total amount of the electrolyte.
[0183] In an embodiment of the invention, the battery according to the invention comprises one or more separators (4) by means of which the electrodes are mechanically separated. Suitable separators (4) are polymer films, in particular porous polymer films, which are non-reactive to metallic lithium. Particularly suitable materials for the separators (4) are polyolefins, in particular film-forming porous polyethylene and film-forming porous polypropylene.
[0184] The membrane (4) made of polyolefin, in particular polyethylene or polypropylene, can have a porosity in the range of 35% to 50%. Suitable pore sizes are, for example, in the range of 30 to 500 nm.
[0185] In another embodiment of the present invention, the separator (4) may be selected from PET nonwovens filled with inorganic particles. Such separators may have a porosity in the range of 40% to 55%. Suitable pore sizes are, for example, in the range of 80 to 750 nm.
[0186] The battery according to the invention may further comprise a housing, which may have any shape, for example the shape of a cubic or cylindrical disk. In one variant, a metal foil configured as a pouch is used as housing.
[0187] The battery according to the invention provides very good discharge and cycling behavior, in particular at high temperatures (45° C. or higher, for example up to 60° C.), in particular with regard to capacity loss.
[0188] The battery according to the invention may comprise two or more electrochemical cells combined with one another, which may be connected in series or in parallel, for example. Preferably they are connected in series. In the battery according to the invention, at least one of the electrochemical cells comprises at least one electrode according to the invention. Preferably, in the electrochemical cells according to the invention, the majority of the electrochemical cells comprise an electrode according to the invention. Even more preferably, in the battery according to the invention, all electrochemical cells comprise an electrode according to the invention.
[0189] The invention further provides for the use of a battery according to the invention in an apparatus, in particular in a mobile device. Examples of mobile devices are vehicles, such as cars, bicycles, aircraft or water vehicles (such as ships or vessels). Other examples of mobile devices are those that are moved manually, such as computers, in particular laptops, telephones or electric hand tools, such as in the construction industry, in particular drills, battery-powered screwdrivers or battery-powered staplers.
[0190] The present invention is presented through working examples and accompanying drawings (see Figure 1 ) for further explanation.
[0191] All coprecipitations were carried out in a 17-liter stirred tank reactor equipped with four inlets but without an overflow system under a N2 atmosphere which was continuously replenished during step (a). All aqueous solutions were made with deionized water. All precipitations were carried out under stirring. On a routine basis, aliquots of the slurry were analyzed for particle size. Description of the drawings:
[0192] Figure 1 :Settings for carrying out the method of the present invention and the comparative method
[0193] A: 800-l-tank reactor
[0194] B: Feed inlet of solution (α.1), (β.1), (γ.1) [Simplified drawing]
[0195] C: Two-stage inclined blade turbine agitator blade (45° angle, 0.4m diameter)
[0196] D: Engine for agitator
[0197] E: Baffle
[0198] F: Transfer of suspension from reactor to clarifier
[0199] G: Transfer suspension from clarifier to reactor
[0200] H: Plate clarifier
[0201] I: Mother liquor containing particles taken out from the reactor via the overflow of the plate clarifier
[0202] F: Cobalt sulfate aqueous solution feed inlet, solution (α2.1)
[0203] Working Example
[0204] Overview:
[0205] A Mastersizer 3000 from Malvern Panalytical GmbH was used. The sample was filled into the device until a light obscuration of between 4.0% and 14.0% was achieved. The corresponding volume-based particle size distribution (PSD) was determined by laser diffraction based on Mie's scattering theory. The refractive index of H2O (as dispersant) was chosen to be 1.33, while the refractive index of the solid phase was chosen to be 2.19.
[0206] I. Preparation of Precursors of the Invention and Comparative Precursors
[0207] I.1 Overview, Step (a)
[0208] Unless expressly stated otherwise, percentages refer to % by weight. Unless expressly stated otherwise, all pH values are determined at 23°C.
[0209] rpm: revolutions per minute
[0210] The following aqueous solutions are available:
[0211] Solution (α.1): NiSO4, CoSO4 and MnSO4 dissolved in deionized water (molar ratio 91:4.5:4.5, total transition metal concentration: 1.45 mol / kg)
[0212] Solution (α.2): NiSO4, CoSO4 and MnSO4 dissolved in deionized water (molar ratio 83:12:5, total transition metal concentration: 1.45 mol / kg)
[0213] Solution (β.1): 25wt% NaOH dissolved in deionized water
[0214] Solution (γ.1): 25 wt% ammonia in deionized water
[0215] I.2 Preparation of the Precursor P-CAM.1 of the Present Invention
[0216] I.2.1 Preparation of seed slurry, step (b1.1):
[0217] A 50 L stirred vessel equipped with baffles and a three-stage pitched blade stirrer (45° blade angle) with a diameter of 0.21 m was charged with 40 liters of deionized water. The stirrer element was activated to achieve an average energy dissipation of 0.8 W / l and the water was heated to 55° C. Thereafter, solution (γ.1) was added to achieve an NH3 concentration of 0.23 w%. The pH of the solution was then adjusted to 12.2 by adding solution (β.1).
[0218] Then, increase the agitator speed and operate constantly at 420rpm (average energy input of about 12.6W / l). Subsequently, start feeding solutions (α.1), (β.1) and (γ.1) at the same time. Adjust the total flow rate of the feed to achieve an average residence time of 7.5 hours. The molar ratio between ammonia and metal is adjusted to 0.17. The flow rate of NaOH is adjusted by the pH value regulating circuit to maintain the pH value in the container at a constant value of 12.35. The instrument is operated continuously to keep the liquid level in the reaction vessel constant. The resulting seed suspension for step (b1.2) is collected by free overflow from the container. The resulting slurry contains a mixed hydroxide of Ni, Co and Mn with an average particle size (D50) of about 110g / l of 3.9μm and a span of 1.28.
[0219] I.2.2 Precipitation, step (b2.1)
[0220] According to Figure 1680l of deionized water is loaded into the setting so that both agitator stages are immersed. The agitator speed is adjusted to 130rpm (0.36W / L), and water is heated to 55°C via a double jacket. During the entire batch, the temperature remains constant at 55°C. Then, 20.9kg of solution (β.1) is added. As the next step, 43kg of the seed slurry from step (b1.1) is added to the mixture so that the initial solid content is about 5g / l. The pH value after adding all the feeds is 11.65. Subsequently, the agitator speed is adjusted to 396rpm (corresponding to 7.9W / l), and the feeding of solution (α.1), (β.1) and (γ.1) is started simultaneously. During batch synthesis, the agitator speed is gradually reduced to the final agitator speed of 220rpm (1.65W / L). The pH was kept constant at 11.5 by adjusting the addition of solutions (β.1) and (γ.1) to obtain an NH3 concentration in the mother liquor of 0.7 w%. The ratio between the reactor volume (800 l) and the volume flow of the total feed (equivalent to the residence time) was initially in such a way that an average residence time of 40 hours would be obtained. However, the feed was gradually increased during the synthesis to reach a final residence time equivalent to 5 hours.
[0221] The clarifier was initially empty. After one hour of reaction time, the suspension was transferred to the clarifier at a volume flow rate of 360 L / h. After 10 minutes, the suspension was transferred from the clarifier back to the reactor at a volume flow rate of 340 L / h. During the above-mentioned gradual increase in feed, the volume flow rates of the suspension transferred to the clarifier and back to the reactor were adjusted to keep the reactor volume constant at 800 L during the entire synthesis.
[0222] Once the clarifier is filled (after about 6 h), the mother liquor containing particles flows out of the tank reactor. During the synthesis, the average particle content of the mother liquor removed by overflow of the plate clarifier was 32 mg / l. The average size (D50) of the particles present in the mother liquor removed was 7.6 μm. SEM micrographs of the particles in the mother liquor volume removed at the end of the synthesis can be seen at Figure 3 middle.
[0223] The entire synthesis duration was 23.5 h, resulting in a solids content of 382 g / L in the reactor, measured via H2SO4 dissolution of the suspension and subsequent ICP analysis of Ni, Co, Mn.
[0224] After the batch was completed, all feed flows were stopped, and the reactor and clarifier were discharged into a stirred suspension buffer vessel, and the slurry was filtered using a filter press. The filter cake was washed with solution (β.1) and deionized water and dried at 120°C for 14 hours to obtain a precursor P-CAM.1 with a molar composition of Ni:Co:Mn=91:4.5:4.5, an average particle size (d50)=13.9 μm and a span=0.31. The cross-sectional SEM photograph of P-CAM.1 shows a core-shell structure containing substantially radially aligned primary particles. A small porous layer is visible between the core and the shell.
[0225] I.3 Preparation of comparative precursor CP-CAM.2
[0226] The protocol of Example P-CAM.1 was followed to some extent, but different feed flow rates were applied. The ratio between the reactor volume (800 l) and the volume flow of the total feed (equivalent to the residence time) was started at 40 hours, and the feed was gradually increased during the synthesis to reach an equivalent final residence time of 9 hours. The lower feed flow rate resulted in a lower hydraulic load on the clarifier, resulting in a different solid-liquid separation behavior. During the synthesis, the average particle content of the mother liquor removed by overflow of the plate clarifier reached an amount of 1.4 mg / l.
[0227] The entire synthesis duration was 43.7 h, resulting in a final solid content of 396 g / L in the reactor, measured via H2SO4 dissolution of the suspension and subsequent ICP analysis of Ni, Co, Mn.
[0228] After the batch was completed, all feed flows were stopped, and the reactor and clarifier were discharged into a stirred suspension buffer vessel, and the slurry was filtered using a filter press. The filter cake was washed with solution (β.1) and DI water and dried at 120°C for 14 hours to obtain a precursor CP-CAM.2 with a molar composition of Ni:Co:Mn=91:4.5:4.5, an average particle size (D50)=14.0 μm and a span=0.37.
[0229] I.4 Preparation of the Precursor P-CAM.3 of the Present Invention
[0230] I.4.1 Making pulped seeds, step (b1.3)
[0231] The protocol of step (b1.1) was followed, but solution (α.2) was used instead of solution (α.1). The resulting slurry contained about 110 g / l of mixed hydroxides of Ni, Co and Mn with an average particle size (D50) of 4.0 μm and a span of 1.32.
[0232] I.4.2 Making pulped seeds, step (b2.3)
[0233] Follow the protocol of step (b2.1), but use solution (a.2) instead of (a.1).
[0234] During step (b2.3), the average particle content of the mother liquor withdrawn through the clarifier was 42 mg / l. The average diameter (D50) of the particles present in the withdrawn mother liquor was 7.2 μm.
[0235] The entire synthesis duration was 22.7 h, resulting in a solids content of 374 g / L in the reactor, measured via H2SO4 dissolution of the suspension and subsequent ICP analysis of Ni, Co, Mn.
[0236] After the batch was completed, all feed flows were stopped, and the reactor and clarifier were discharged into a stirred suspension buffer container, and the slurry was filtered using a filter press. The filter cake was washed with solution (β.1) and deionized water and dried at 120°C for 14 hours to obtain a precursor P-CAM.2 with a molar composition of Ni:Co:Mn=83:12:5, an average particle size (D50)=14.1 μm and a span=0.27. The cross-sectional SEM photograph of P-CAM.3 shows a core-shell structure containing substantially radially aligned primary particles. A small porous layer is visible between the core and the shell.
[0237] I.5 Preparation of comparative precursor CP-CAM.4
[0238] The protocol of Example CP-CAM.2 was essentially followed. During the synthesis, the mother liquor removed via the clarifier reached an average particle content of 1.2 mg / l.
[0239] The entire synthesis duration was 41.6 h, resulting in a final solid content of 381 g / L in the reactor, measured via H2SO4 dissolution of the suspension and subsequent ICP analysis of Ni, Co, Mn.
[0240] After the batch was completed, all feed flows were stopped, and the reactor and clarifier were discharged into a stirred suspension buffer vessel, and the slurry was filtered using a filter press. The filter cake was washed with solution (β.1) and deionized water and dried at 120°C for 14 hours to obtain a precursor CP-CAM.4 with a molar composition of Ni:Co:Mn=83:12:5, an average particle size (d50)=13.8 μm and a span=0.36.
[0241] II. Synthesis of cathode active materials
[0242] II.1 Manufacturing of CAM.1 of the present invention
[0243] P-CAM.1 was mixed with LiOH at a Li / TM molar ratio of 1.04 and calcined in a laboratory Linn furnace at 765°C for 8 hours. After natural cooling to ambient temperature, the resulting CAM.1 was deagglomerated in a laboratory mill. The resulting CAM.1 had an average particle size of 13.7 μm and a span of 0.30.
[0244] II.2 Comparison of the manufacturing of C-CAM.2
[0245] CP-CAM.2 was mixed with LiOH at a Li / TM molar ratio of 1.04 and calcined in a laboratory Linn furnace at 765°C for 8 hours. After natural cooling to ambient temperature, the resulting C-CAM.2 was deagglomerated by a laboratory mill. The resulting C-CAM.2 had an average particle size of 13.9 μm and a span of 0.36.
[0246] In electrochemical cells / lithium-ion batteries, cathodes containing CAM.1 have superior properties compared to cathodes containing C-CAM.2.
[0247] II.3 Manufacturing of CAM.3 of the present invention
[0248] P-CAM.3 was mixed with LiOH at a Li / TM molar ratio of 1.04 and calcined in a laboratory Linn furnace at 780°C for 8 hours. After natural cooling to ambient temperature, the resulting CAM.1 was deagglomerated in a laboratory mill. The resulting CAM.3 had an average particle size of 13.9 μm and a span of 0.26.
[0249] II.4 Comparison of the manufacture of C-CAM.4
[0250] CP-CAM.4 was mixed with LiOH at a Li / TM molar ratio of 1.04 and calcined in a laboratory Linn furnace at 780°C for 8 hours. After natural cooling to ambient temperature, the resulting C-CAM.4 was deagglomerated in a laboratory mill. The resulting C-CAM.2 had an average particle size of 13.6 μm and a span of 0.35.
[0251] In electrochemical cells / lithium-ion batteries, cathodes containing CAM.3 have superior properties compared to cathodes containing C-CAM.4.
Claims
1. A method for producing a particulate (oxy)hydroxide of TM, wherein the method comprises a combination of nickel and at least one metal selected from Co and Mn, and wherein the method comprises the following steps: (a) providing an aqueous solution (α) of one or more water-soluble salts containing Ni and at least one transition metal selected from Co and Mn and optionally at least one additional metal selected from Ti, Zr, Mo, W, Al, Mg, Nb and Ta and an aqueous solution (β) containing an alkali metal hydroxide and optionally an aqueous solution (γ) containing a complexing agent, (b) combining solution (α) and solution (β) and, if applicable, solution (γ) in a stirred tank reactor at a pH value in the range of 10.5 to 12.5 determined at 23° C. in one or more sub-steps, thereby forming solid particles of the hydroxide, said solid particles being slurried, The stirred tank reactor used in step (b) or at least one of the sub-steps (b) is equipped with a solid-liquid separation device, through which a mother liquor containing slurried hydroxide particles in the range of 2 mg / l to 20 g / l is taken out.
2. The method according to claim 1, wherein: TM is a metal combination according to the general formula (I) (Ni a Co b Mr c ) 1-d M d (I) in a is in the range of 0.6 to 0.95, b is in the range of 0.025 to 0.2, c is in the range of 0 to 0.2, and d is in the range of 0 to 0.1, M is selected from the group consisting of Mg, Al, Ti, Zr, Mo, W, Al, Mg, Nb and Ta, a+b+c=1.
3. The method according to claim 1, wherein: TM is a metal combination according to the general formula (I a) (Ni a Co b Mr c ) 1-d M d (I a) in a is in the range of 0.25 to 0.4, b is in the range of 0 to 0.2, c is in the range of 0.6 to 0.75, and d is in the range of 0 to 0.1, M is selected from the group consisting of Mg, Al, Ti, Zr, Mo, W, Nb and Ta, a+b+c=1.
4. A method according to any one of the preceding claims, wherein: Step (b) is carried out in two or more sub-steps, (b1) and (b2), wherein: Sub-step (b1) comprises combining solution (α) and solution (β) and, if applicable, solution (γ) in a continuously operated stirred tank reactor at a pH value in the range of 12.0 to 12.5 determined at 23° C., thereby forming solid particles of the hydroxide, said solid particles being slurried, and Sub-step (b2) comprises transferring the slurry from step (b) into a stirred tank reactor, in which solution (α) and solution (β) and, if applicable, solution (γ) are combined with the slurry at a pH value in the range of 11.0 to 12.0 determined at 23° C., And wherein the stirred tank reactor used in sub-step (b2) is equipped with a solid-liquid separation device, through which the mother liquor containing slurried hydroxide particles in the range of 2 mg / l to 20 g / l is taken out.
5. A method according to any one of the preceding claims, wherein: The average particle size (D50) of the precursor removed in step (b) is in the range of 0.5 to 20 μm.
6. A method according to any one of the preceding claims, wherein: In step (b), mother liquor removal is carried out using a clarifier or at least one candle filter.
7. A granular (oxy)hydroxide of TM, wherein TM refers to a combination of nickel and at least one metal selected from cobalt and manganese, wherein the granular (oxy)hydroxide has an average particle size (d50) in the range of 3 to 20 μm and a core-shell structure, wherein both the core and the shell exhibit substantially radial alignment of the lamellar primary particles and wherein the core and the shell are separated by a porous layer containing randomly arranged primary particles, and wherein the granular (oxy)hydroxide has a particle size distribution with a span [(D90)–(D10)] / (D50) in the range of 0.2 to 0.
33.
8. The granular (oxy)hydroxide according to claim 7, wherein TM is a metal combination according to the general formula (I) (Ni a Co b Mr c ) 1-d M d (I) in a is in the range of 0.6 to 0.95, b is in the range of 0.025 to 0.2, c is in the range of 0 to 0.2, and d is in the range of 0 to 0.1, M is selected from the group consisting of Mg, Al, Ti, Zr, Mo, W, Nb and Ta, a+b+c=1.
9. The granular (oxy)hydroxide according to claim 7, wherein TM is a metal combination according to formula (Ia) (Ni a Co b Mr c ) 1-d M d (I a) in a is in the range of 0.25 to 0.4, b is in the range of 0 to 0.2, c is in the range of 0.6 to 0.75, and d is in the range of 0 to 0.1, M is selected from the group consisting of Mg, Al, Ti, Zr, Mo, W, Nb and Ta, a+b+c=1.
10. The particulate (oxy)hydroxide according to any one of claims 7 to 9, wherein The porous layer between the core and the shell has an average thickness in the range of 0.1 to 1.0 μm.
11. The granular (oxy)hydroxide according to any one of claims 7 to 11, wherein The span is in the range of 0.21 to 0.
29.
12. A method for producing a cathode active material, the method comprising the steps of: The particulate (oxy)hydroxide according to any one of claims 7 to 11 is mixed with a lithium source and, if applicable, a hydroxide or oxide of at least one of Mg, Al, Ti, Zr, Ta, Nb, Mo, W and subsequently calcined at a temperature in the range of 700° C. to 900° C.
13. A method for producing a cathode active material, the method comprising the steps of: The particulate (oxy)hydroxide according to any one of claims 7 to 11 is heated to a temperature in the range of 400°C to 600°C in the absence of a lithium source to obtain an oxide of TM, followed by mixing the obtained oxide of TM with a lithium source and, if applicable, a hydroxide or oxide of at least one of Mg, Al, Ti, Zr, Ta, Nb, Mo, W, and then calcining at a temperature in the range of 700°C to 900°C.
14. A method according to the general formula Li 1+x TM 1-x A granular cathode active material of O2, wherein TM refers to a combination of nickel and at least one metal selected from cobalt and manganese and optionally at least one metal selected from at least one of Mg, Al, Ti, Zr, Ta, Nb, Mo, W, wherein x is in the range of 0 to 0.03, and wherein the cathode active material has an average particle size (D50) of 3 to 20 μm and a particle size distribution with a span [(D90)–(D10)] / (D50) in the range of 0.2 to 0.
33.
15. The particulate cathode active material according to claim 14, wherein The span is in the range of 0.21 to 0.
29.
16. The cathode active material according to claim 14 or 15, wherein TM is a metal combination according to the general formula (I) (Ni a Co b Mr c ) 1-d M d (I) in a is in the range of 0.6 to 0.95, b is in the range of 0.025 to 0.2, c is in the range of 0 to 0.2, and d is in the range of 0 to 0.1, M is selected from the group consisting of Mg, Al, Ti, Zr, Mo, W, Nb and Ta, a+b+c=1.
17. A cathode comprising: (A) at least one cathode active material according to any one of claims 14 to 16, (B) carbon in an electrically conductive form, and (C) at least one adhesive.
Citation Information
Patent Citations
Nickel composite hydroxide and process for producing same, positive active material for nonaqueous-electrolyte secondary battery and process for producing same, and nonaqueous-electrolyte secondary battery
EP2720305A1
Nickel composite hydroxide and method for producing same, positive electrode active material for nonaqueous electrolyte secondary batteries and method for producing same, and nonaqueous electrolyte secondary battery
EP2818452A1